Effect of biodegradable hydrogels on moisture retention and germination of alfalfa - Laredo-Alcalá, Elan Iñaky; Salinas-Gutiérrez, Azael; Chávez- Martínez, Mónica Lizeth; Meléndez- Rentería, Norma Paola; Barrera- Martínez, Cynthia Lizeth; Salinas-Jasso, Thalía Athenas; De León-Zapata, Miguel Ángel (Ecosistemas y Recursos Agropecuarios, 2023)
Biodegradable hydrogels obtained from natural sources are non-toxic materials with a large water retention capacity, hence a valuable alternative for the rational use of water in agriculture applications. The aim of the present work was to evaluate the effect of hydrogels formulated from natural polymers (alginate, nopal polysaccharides, aloe polysaccharides, and chitosan) on water retention capacity, biodegradable potential as well as the morphometry and germination of alfalfa seedlings compared with potassium polyacrylate hydrogel (commercial control). A total of 36 treatments were characterized under controlled conditions at the laboratory level obtaining that in comparison with the commercial control, PSGCL hydrogel presented the highest water retention value, whereas all the hydrogels obtained from natural polymers had greater biodegradable potential. Regarding to germination of alfalfa seedlings, PSGP hydrogel presented the most outstanding performance in term of percentage of germination, plant height and foliage development with respect to absolute control and the rest of the treatments.